2015
DOI: 10.1515/agp-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

Upper Devonian microvertebrates from the Canning Basin, Western Australia

Abstract: A diverse microvertebrate fauna is described from the Virgin Hills and Napier formations, Bugle Gap Limestone Canning Basin, Western Australia. Measured sections at Horse Spring and Casey Falls (Virgin Hills Formation) and South Oscar Range (Napier Formation) comprise proximal to distal slope carbonates ranging in age from the Late Devonian Frasnian to middle Famennian. A total of 18 chondrichthyan taxa are identified based on teeth, including the first record of Thrinacodus tranquillus, Cladoides wildungensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 72 publications
2
13
0
Order By: Relevance
“…Very similar is the collection of specimens from Horse Spring in the Canning Basin area, north-western Australia, recently described by Roelofs et al (2015). Here, among 34 shark teeth from five samples dated as jamieae-Lower rhenana Conodont zones (MN11 Montagne Noire zone), 31 belong to at least three species of Phoebodus (including strange, probably juvenile teeth of Ph.…”
Section: Discussionsupporting
confidence: 69%
“…Very similar is the collection of specimens from Horse Spring in the Canning Basin area, north-western Australia, recently described by Roelofs et al (2015). Here, among 34 shark teeth from five samples dated as jamieae-Lower rhenana Conodont zones (MN11 Montagne Noire zone), 31 belong to at least three species of Phoebodus (including strange, probably juvenile teeth of Ph.…”
Section: Discussionsupporting
confidence: 69%
“…(Wheeley et al, 2012). Subsequent work by Trotter et al (2015) showed an average offset of 0.6 ± 0.2 ‰ between the two methodologies, similar to earlier work of 0.7 ‰ (Trotter et al, 2008 (Becker, 2000), conodont (Nicoll and Druce, 1979;Klapper, 2006) and vertebrate microfossil taxa (Turner, 1982;Trinajstic and George, 2009;Hairapetian et al, 2015;Roelofs et al, 2015Roelofs et al, , 2016 in the Late Devonian and Early Carboniferous suggests that pathways existed for significant faunal exchange. Furthermore, the recovery, from the Lennard Shelf, of globally correlative carbon isotope signatures associated with the Kellwasser Event (Stephens and Sumner, 2003;Playton et al, 2013;George et al, 2014;Hillbun et al, 2015), and presence of a significant regression (Talent et al, 1993) and negative δ 13 C excursion (Andrew et al, 1994) = +21.7 ‰) from latitudinally equivalent sites reported in Joachimski et al (2004Joachimski et al ( , 2009 elements tested was +20.4 ±0.9 ‰.…”
Section: -supporting
confidence: 78%
“…Upper Devonian vertebrate microfossils are common in the distal slope facies of the Virgin Hills Formation (late Frasnian -middle Famennian; Fig. 1; Playford et al, 2009;Trinajstic and George, 2009;Trinajstic et al, 2014;Roelofs et al, 2015) and in the conodont-poor facies of the Fairfield Group (Upper Devonian-Lower Carboniferous) (Roelofs et al, 2016;Thomas, 1957Thomas, , 1959. Twenty kilogram samples were collected from single beds at Horse Spring (18°11′41′′ S, 126°01′69′′ E) (sample prefix VHS), Oscar Hill (18°04'07" S, 125°26'41" E) (sample prefixes OH, Si) and Laurel Downs (18°01'37" S, 125°18'43" E) (sample prefixes 1984,…”
Section: Sample Collection Processing and Imagingmentioning
confidence: 99%
“…The Canning Basin was thus situated at the junction of major terranes and is therefore an ideal study area to evaluate Late Devonian faunal exchanges between these landmasses. Common faunal components between the Canning Basin and areas in South China and south-east Asia are known for several vertebrate groups from the Late Devonian, including placoderms (Young, 1984;Young et al, 2010) and chondrichthyans (Trinajstic and George, 2009;Roelofs et al, 2015). In addition, the jawless thelodonts are known from the uppermost Devonian in Iran (Hairapetian et al, 2015) North Gondwana and north-western Australia (Trinajstic, 2001;Hairapetian et al, 2015).…”
Section: Introductionmentioning
confidence: 99%